Natural small molecules as inhibitors of coronavirus lipid-dependent attachment to host cells: a possible strategy for reducing SARS-COV-2 infectivity? SARS-COV-2 lipid-dependent attachment to host cells - Baglivo, Mirko; Baronio, Manuela; Natalini, Giuseppe; Beccari, Tommaso; Chiurazzi, Pietro; Fulcheri, Ezio; Petralia, Paolo Pietro; Michelini, Sandro; Fiorentini, Giovanni; Miggiano, Giacinto Abele; Morresi, Assunta; Tonini, Gerolamo; et al. (Acta Biomedica Atenei Parmensis, 2020)
Background: Viral infectivity depends on interactions between components of the host cell plasma membrane and the virus envelope. Here we review strategies that could help stem the advance of the SARS-COV-2 epidemic. Methods and Results: We focus on the role of lipid structures, such as lipid rafts and cholesterol, involved in the process, mediated by endocytosis, by which viruses attach to and infect cells. Previous studies have shown that many naturally derived substances, such as cyclodextrin and sterols, could reduce the infectivity of many types of viruses, including the coronavirus family, through interference with lipid-dependent attachment to human host cells. Conclusions: Certain molecules prove able to reduce the infectivity of some coronaviruses, possibly by inhibiting viral lipid-dependent attachment to host cells. More research into these molecules and methods would be worthwhile as it could provide insights the mechanism of transmission of SARS-COV-2 and, into how they could become a basis for new antiviral strategies.